Rozwój komputerów osobistych i technologii internetowych - szansa dla obszarów wiejskich i słabo zurbanizowanych - Karwowski, Waldemar; Orłowski, Arkadiusz (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2003)
In the paper short history of Internet in Poland was presented. In the next part, state and basic barriers of access to computer equipment and Internet were discussed. In the paper also description of Internet role in providing for the social and economic needs was included. Particular behaviours and expectations of clients and customers using the Internet and main benefits following from this form of providing for the social and economic needs were discussed. Menaces and perspectives of using Internet in information society were summarizedlw.